Investigation of Gas Permeability in Carbon Nanotube (CNT)-Polymer Matrix Membranes via Modifying CNTs with Functional Groups/Metals and Controlling Modification Location - Ge, L.; Zhu, Z.; Li, F.; Liu, Shaomin; Wang, L.; Tang, X.; Rudolph, V. (American Chemical Society, 2011)
Metal- or functional group-modified multiwalled carbon nanotubes (CNTs) were embedded into the poly(ether sulfone) (PES) polymer matrix to study the gas permeability of the nanocomposite membranes. Carboxyl-functionalized CNTs and Ru (Fe) metal-modified CNTs were prepared via acid oxidation and wet impregnation methods, respectively. The derived nanocomposite membranes show similar crystalline structure and CNT dispersion as well as improvement in gas permeation fluxes at low CNT concentration (<5 wt %). However, the CO2/N2 selectivity varies with different modification components. Compared with pure polymer membranes, those containing Ru-modified CNTs show higher gas selectivity, while Fe-modified CNT membranes show lower selectivity, and carboxyl CNT composite membranes are similar to pure PES membrane. By controlling Ru modification into CNT channels, poor gas selectivity of the corresponding membranes is observed. These results, combined with the results of density functional theory calculations, indicate that different gas adsorption behaviors are introduced via modification by metals or carboxyl functional groups and further influence the gas permeability. Based on both experimental and theoretical results, gas diffusion appears to pass through the interface between polymer chains and carbon nanotubes, rather than the CNT channels, in this nanocomposite system. Thereby, tailoring modification on the external surface of carbon nanotubes can be more effective for improving gas separation performance of CNT-based nanocomposite membranes.